Anisotropic Magnetoresistivity in Semimetal TaSb2 - 刘夏吟 王嘉璐 尤伟 王婷婷 杨海洋 焦文鹤 毛宏颖 张莉 程杰 李玉科 (中国物理快报：英文版, 2017)
We investigate the anisotropic magnetic transports in topological semimetal TaSb2. The compound shows the large magnetoresistance(MR) without saturation and the metal-insulator-like transition no matter whether the magnetic field is parallel to c-axis or a-axis, except that the MR for B‖c is almost twice as large as that of B‖a at low temperatures. The adopted Kohler’s rule can be obeyed by the MR at distinct temperatures for B‖c,but it is slightly violated as B‖a. The angle-dependent MR measurements exhibit the two-fold rotational symmetry below70 K,consistent with the monoclinic crystal structure of TaSb2. The dumbbell-like picture of angle-dependent MR in TaSb2 suggests a strongly anisotropic Fermi surface at low temperatures. However, it finally loses the two-fold symmetry over 70 K, implying a possible topological phase transition at around the temperature where Tm is related to a metal-insulator-like transition under magnetic fields.